The Life Cycle Assessment Method Used to Predict the Rubber Industry's Environmental Impact - Nia Armelia Putri; Dessy Maya Sari; Delfia Fansyah; Aulia Rachma Yuliani; Pertiwi Andarani; Ariyanti Sarwono (Journal of Sustainable Infrastructure, 2022)
Natural rubber is one of the agricultural products in exceptionally high demand for industrial materials. In Indonesia, rubber is a major plantation crop grown all across the country. This research seeks to use the LCA technique, but its primary objective is to examine the consequences of the crumb rubber industry. Using sulfuric acid causes the emission of roughly 11,94705 kg equivalent of the gas sulfur dioxide into the environment. In contrast, using isoprene as a base material causes the emission of approximately 1090 kg equivalent to the gas carbon dioxide. Coal-derived energy accounts for up to 719,748 MJ, or 199,930 kWh, and is the critical focus in the quest for alternative energies. Because the macerator, creeper, hammer mill, and drying machine take 199.93-kWh of electricity to operate.